Application of singular spectrum analysis and multilayer perceptron in the mid-long-term polar motion prediction. Issue 9 (1st November 2021) - Jin, Xin; Guo, Jinyun; Shen, Yi; Liu, Xin; Zhao, Chunmei
Abstract: Long-term prediction parameters of polar motion (PM) with high precision have an important significance in understanding Earth geophysical processes in the future. The multilayer perceptron (MLP) is introduced into PM prediction and we try for the first time to combine MLP with autoregressive moving average model (ARMA) and singular spectrum analysis (SSA) for the mid-long-term prediction of PM. The principal components of PM were extracted and predicted by SSA first. Then, the combined MLP and ARMA were used to predict the residual term. The PM predictions were obtained by adding the principal components and the residual predictions. Applying this proposed method, 157 500-day and 12 5-year lead time predictions of PM were made based on IERS 14 C04 product. The results showed that the proposed method performed well in the mid-long-term period of PM predictions, which was superior to IERS Bulletin A.